2008
DOI: 10.1002/bjs.6198
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the need for nasogastric or nasojejunal decompression after gastrectomy for gastric cancer

Abstract: Routine nasogastric or nasojejunal decompression is unnecessary after gastrectomy for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 19 publications
2
43
0
5
Order By: Relevance
“…Many clinical studies have suggested that this practice does not provide any benefit but could increase patient discomfort and respiratory complications [1][2][3]. Furthermore, three recent meta-analyses concluded that nasogastric or nasojejunal decompression does not promote the recovery of gastrointestinal function or reduce the incidence of postoperative complications after gastrectomy for gastric cancer and after abdominal surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical studies have suggested that this practice does not provide any benefit but could increase patient discomfort and respiratory complications [1][2][3]. Furthermore, three recent meta-analyses concluded that nasogastric or nasojejunal decompression does not promote the recovery of gastrointestinal function or reduce the incidence of postoperative complications after gastrectomy for gastric cancer and after abdominal surgery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the group of patients that did not use NGI, had an earlier return of the intestinal function and lower index of pulmonary complications. However, in surgical procedures in the upper abdomen with higher gastric dilation risk or prolonged ileum (esophagectomies, gastroduodenopancreatectomies, ileal pouchs) still persists its indication for the shortest time possible, observing the cares described above 19,27,28 .…”
mentioning
confidence: 99%
“…Some clinical studies and meta-analyses have suggested that nasogastric decompression does not provide any benefit but on the contrary it could increase patients’ discomfort and respiratory complications after gastrectomy [4,5,6,7]. However, the application of nasogastric decompression has been taken into consideration by most surgeons in order to decrease the incidence of postoperative anastomotic or duodenal stump leak, wound and pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%